Persistence and Progression of Immunologic Abnormalities in Haemophilia - Gill, Joan C; Wheeler, Dana; Menitove, Jay E; Aster, Richard H; Casper, James T; Kirchner, Phyllis; Montgomery, Robert R (Thrombosis and Haemostasis, 1985)
Immunologic parameters in 51 patients with haemophilia treated with cryoprecipitate from volunteer donors or with commercial lyophilized concentrate were studied on 2–7 occasions. Concentrate users had significantly decreased mean T4 (helper)/T8 (suppressor) lymphocyte ratios when the initial (1.5 ± .43) and most recent (1.25 ± .60) values were compared (p <.001), whereas in cryoprecipitate users mean values remained normal. Of the 22 concentrate users with initially normal T4/T8 ratios, 10 became abnormal during the study, an incidence of 45%. Fifteen of 28 (54%) patients with abnormal T4/T8 ratios had elevated circulating immune complexes (CIC), whereas all 16 patients with normal T4/T8 ratios had normal levels of CIC. Six patients have persistent lymphadenopathy.
Keywords: Haemophilia; Acquired immune deficiency; Immune complexes; Lymphocyte subsets; Therapeutic clotting factor replacement